Describing different integrated solutions. (2018) - Jagstedt, Siri; Persson, Magnus
Integrating products and services seamlessly into a solution enables a more valuable offering to be created, described as an integrated solution. This paper investigates how various dimensions can be used to describe different integrated solutions, expanding the knowledge on how such solutions co-exist within different companies and how they can be described. A case study involving two companies shows that different integrated solutions correspond to different ways of relating to three dimensions: addressing the customer, integration and customisation.